(3SfG GdegJOi Edi eaGNQI GdhRjQ CHj GdYHGS GdjMeOis - (3Ydj Hf CMeO Hf bGSe Hf ehSi GHf eUHGM GdRQhjdj,J (B1136 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj edcfG CYfI GdHjGf , hCjOfG HYLGFH GdJHjGf s
(3Cdag aj eaGNQ GdhRjQ CHj YHOGddg Hf GdMSf Hf CMeO Hf eMeO GdjMeOj ef hRQGA GdOhdI GdYdhjI GdgGTejI HGdeZQHs
(3hGdejcQhajde JGdas
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B259 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B23s
Keywords: (3GdJGQjNs